A Malaysian perspective on the impact of protection motivation behaviours on robo-advisor adoption during financial crises / Najihah Abd Razak and Kamisah Ismail - Abd Razak, Najihah; Ismail, Kamisah (UiTM Press, 2024)
The study integrated the Protection Motivation Theory into the Technology Acceptance Model to explore factors influencing robo-advisory service adoption. Robo-advisor adoption among retail investors in Malaysia was low during financial crises like COVID-19, necessitating an investigation into adoption determinants. Little is known about the drivers of robo-advisor adoption during financial crises and how investors perceive the effectiveness and reliability of AI-assisted services in such circumstances. The study contributes to existing literature by shedding light on investors' protection behaviors and AI adoption in the financial sector during challenging economic times. Quantitative data from 128 respondents revealed that response efficacy influences perceived usefulness, impacting investors' intentions to use robo-advisors. Behavioral intention significantly predicted actual usage during crises like COVID-19, highlighting challenges in translating knowledge into action. The study enhances understanding of investors’ decision-making and offers insights for policymakers and financial services providers, amid evolving financial landscapes.